2022
DOI: 10.1016/j.annemergmed.2022.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Parental Acceptance of COVID-19 Vaccination: A Multicenter Pediatric Emergency Department Cross-Sectional Analysis

Abstract: Objective At a time when the COVID19 vaccine was approved for everyone > 12 years of age, we sought to identify characteristics and beliefs associated with COVID-19 vaccination acceptance. Methods We conducted a cross-sectional survey study of parents of children aged 3-16 years presenting to one of 9 emergency departments from June-August 2021 to assess parental acceptance of COVID-19 vaccines. Using multiple variable regression, we ascertained which factors were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
9
10
0
Order By: Relevance
“…Our finding that younger parents were more likely to be undecided or without intention to vaccinate is consistent with other studies as well. 16,19,21 Similarly, lesser education and lower income also were related to being undecided or without intention to vaccinate and are similar to previous investigations. 18,19,21 Together these findings suggest that younger and more economically disadvantaged parents remain concerned, and need additional safety and effectiveness information about vaccinating their children for COVID-19.…”
Section: Figure 3: Factors Informing Parent's Decision To Have Their ...supporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that younger parents were more likely to be undecided or without intention to vaccinate is consistent with other studies as well. 16,19,21 Similarly, lesser education and lower income also were related to being undecided or without intention to vaccinate and are similar to previous investigations. 18,19,21 Together these findings suggest that younger and more economically disadvantaged parents remain concerned, and need additional safety and effectiveness information about vaccinating their children for COVID-19.…”
Section: Figure 3: Factors Informing Parent's Decision To Have Their ...supporting
confidence: 88%
“…16,19,21 Similarly, lesser education and lower income also were related to being undecided or without intention to vaccinate and are similar to previous investigations. 18,19,21 Together these findings suggest that younger and more economically disadvantaged parents remain concerned, and need additional safety and effectiveness information about vaccinating their children for COVID-19. We also observed that residents of Los Angeles County reported more hesitant or less likely to vaccinate their children although this observation lost significance in multivariate analyses.…”
Section: Figure 3: Factors Informing Parent's Decision To Have Their ...supporting
confidence: 88%
“… [5] , [6] Trust in scientists has also been reported as a key factor in parental vaccine acceptance. [7] A perception that vaccination is not necessary due to low risk of complications as well as concern about vaccine side effects have been reported as reasons for parents not intending to vaccinate children. [8] …”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has evaluated parental intention to vaccinate their children against SARS-CoV-2 in Canada 2 4 , 6 8 and internationally, 9 16 but few studies have explored parents’ decisions to have their children vaccinated or not, once eligible. 17 Given the observed discrepancy between parental intention and decision to seek vaccination for their children against SARS-CoV-2, it is critical to investigate how and why parents make their decisions. Understanding the factors that influence parents to seek vaccination against SARS-CoV-2 for their children, or not, would help inform policies and interventions focused on this population and would help health care professionals understand parents’ perspectives and concerns.…”
mentioning
confidence: 99%